The laughing policebot: automation and the end of policing - McGuire, M. R. (Policing and society, 2021)
Though there has always been a close relationship between professional policing and technology, the sheer scale of operational dependence upon new technologies has begun to raise a number of concerns. In this paper I trace 3 kinds of contrasting dynamics in the perception of the policing/technology relationship. A first view has tended to see this relationship in largely unproblematic, positive terms, one which generally results in ‘more efficient’, cost-effective forms of policing. Against this, a more sceptical position can also be traced. On this view, whilst enhanced access to technology often benefits police performance, it has often also come with enhanced opportunities for misuse which threaten dystopian scenarios of coercion, denial of rights and – at worst – the spectre of technologised police states. I argue that a third view is now plausible, one that has been far less discussed, even though it may present the greatest challenge to the viability of policing as we have known it. For the emergent technologies now reshaping policing often involve automated tools like predictive algorithms or facial recognition systems. This raises the question of what limits to the automation of policing there may be and whether automation will ultimately entail the ‘end’ of professional police forces as once envisioned by Peel.